2019
DOI: 10.1177/0391398819882697
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research on individualized hemodialysis preventing unconventional hypotension in diabetic nephropathy patient

Abstract: Objective: This study aims to evaluate the effectiveness of individualized hemodialysis for unconventional hypotension in diabetic nephropathy patients. Methods: A total of 60 patients were selected and randomly divided into study group and control group. The control group used the standard dialysis model, while the study group used the individualized hemodialysis scheme, in which the dialysis was performed using an individualized dialysis machine temperature control, pattern of natrium, and pattern of step ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…Some researchers have focused on the recognition of modifiable predictors of intradialytic HD-related symptoms. According to clinical trials, hypotension is the most common complication occurring in dialysis sessions with symptoms such as dizziness, fatigue, and nausea [11][12][13][14][15] (Figures 1 and 2). One of the analyzed research studies in 2014 (44,801 HD treatment sessions with a number of 1,137 patients) showed 75.1% hypotension occurrence [16].…”
Section: Intradialytic Complicationsmentioning
confidence: 99%
“…Some researchers have focused on the recognition of modifiable predictors of intradialytic HD-related symptoms. According to clinical trials, hypotension is the most common complication occurring in dialysis sessions with symptoms such as dizziness, fatigue, and nausea [11][12][13][14][15] (Figures 1 and 2). One of the analyzed research studies in 2014 (44,801 HD treatment sessions with a number of 1,137 patients) showed 75.1% hypotension occurrence [16].…”
Section: Intradialytic Complicationsmentioning
confidence: 99%